Doppler ultrasound in obstetrics. Issue 6 (June 2019) - White, Victoria A.; Mahendru, Amita A.
Abstract: Doppler ultrasound is used to monitor high-risk pregnancies and time delivery appropriately. Pregnancies with high resistance in the uterine arteries (UtA) are at risk of pre-eclampsia and fetal growth restriction and need close monitoring. Resistance within the umbilical arteries (UmA) reflects the resistance to blood flow within the placenta. In a poorly functioning placenta, resistance will gradually increase and umbilical arterial flow will eventually become reversed at the end of diastole. A chronically hypoxic fetus will dilate its cerebral arteries to divert blood to the brain. This will be demonstrated by a falling resistance in the middle cerebral arteries (MCA). This compensatory mechanism can be monitored by measuring the resistance within these vessels. The ductus venosus (DV) Doppler can be used to monitor fetuses with an abnormal UmA doppler in whom delivery is not yet appropriate. At extreme pre-term gestation delivery should be planned dependent on changes in the DV blood flow.